PERINATAL OUTCOME OF IUGR FETUSES HAVING NORMAL AND ABNORMAL UMBILICAL ARTERY DOPPLER STUDY - Zonia Zaman; Fatima Imran; Aurangzeb Bantth (Journal of University Medical & Dental College, 2016)
ABSTRACT: OBJECTIVE: To compare the perinatal outcome of IUGR fetuses having normal and abnormal umbilical artery Doppler study. Study Design: Descriptive Case series study Place and Duration of Study: This study was conducted from March2015 to February2016 in departments of radiology and obstetrics & gynecology Aziz Fatimah hospital Faisalabad. Methodology: In this study a total of 172 pregnant women with diagnosed IUGR between 2840 weeks were included. These patients were divided in to two groups, first group was consisted on 94 pregnant women with IUGR and having normal Doppler ultrasound and second group consisted of 78 women with diagnosed IUGR and having abnormal Doppler ultrasound findings. The IUGR was diagnosed by ultrasonography having estimated weight <10th percentile for gestational age. All the patients in study were followed till delivery and maternal and fetal outcomes were noted in both groups. RESULT: The mean age of group I was 26±5.25 years, and group II was 25±4.18 years. Normal vaginal deliveries were significantly higher (56.38% vs 24.36%, p-value < 0.001) in normal UA Doppler group and C-section rate was significantly (75.64% vs 43.62%) greater in abnormal UA Doppler group. The rate of good APGAR score (> 7) was significantly higher at one minute (75% vs 44.87%, p-value < 0.001) and 5 minute (91.5% vs 71.79%, p-value < 0.001) in women having normal UA Doppler study findings. There were significantly more (58.97 vs 17.02%, p-value < 0.001) preterm deliveries with abnormal doppler study. Birth weight of the babies in abnormal UA Doppler findings was significantly (p-value < 0.001) less with mean weight of 945±168 grams as compared to mean birth weight of 1585±223 grams of babies of normal UA Doppler study. NICU admissions (71.79% vs 20.21%, p-value < 0.001) were significantly greater in women having abnormal UA Doppler findings. Conclusion: There is a strong relationship between perinatal outcome and umbilical artery Doppler velocimetry. With abnormal UA Doppler there are significantly greater chances of adverse perinatal outcome.